Manakiban tradition of Sayyidah Khadijah al-Kubra at Mushalla Daruttaqwa Samarinda, East Borneo, Indonesia - Adyatama, Muhammad Fajar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This paper examines the manaqib tradition of Umm al-Mu’minin, Sayyidah Khadijah al-Kubra in Mushalla Daruttaqwa, Sempaja, Samarinda. The tradition of occasionally reading manaqib has a historical context within the culture and psychology of the community and has produced definite behavioural changes in some or all aspects of the lives of those who engage in it. The manaqib tradition in Mushalla Daruttaqwa is held at ba’da maghrib on every 11th of the qamariyah month (Hijri year). This date is chosen as it coincides with the date of the death of Sayyidah Khadijah al-Kubra, namely on the 11th of Ramadan in the 10th year of the prophethood, three years before the Prophet’s migration to Yathrib (Medina). Sayyidah Khadijah died at the age of 65 when the Prophet was around 50 years old. This manaqib is conducted with sources that are in accordance with the guidance of Tuan Guru. The wisdom for the culture of our ancestors, provided it does not conflict with the texts of the Qur’an and Hadith, expects an abundance of blessings from Sayyidah Khadijah al-Kubra, including for people who love the auliya of Allah, especially the experts of the Prophet’s temple (ahl al-bayt). The activity also has elements and values of moral education, including as a forum for community gathering, as well as motivating children, in particular, to become part of the prosperity of violators and Islamic symbols.